Pengaruh Faktor Kompetensi Individu, Faktor Dukungan Organisasi, Faktor Dukungan Manajemen terhadap Kinerja Pegawai - Jamilatun Hikmah; Slamet Bambang Riono; Muhammad Syaifulloh; Nur Khojin; Nur Aisyah (Program Studi Manajemen Universitas Muhadi Setiabudi, 2019)
This study aims to analyze the influence of individual competence factors, organizational support factors, management support factors on employee performance (case study at grand dian hotel). This study used a saturated sampling technique, a sample of 128 respondents of Grand Dian Hotel employees was used. This research method is obtained from a questionnaire (primary). The analysis technique uses multiple linear regression with the hypothesis test of the stimulant statistical test (F test) and the t statistical test (t test). The results showed that the variable of individual competency factors did not have a significant effect on the performance of Grand Dian Hotel employees. The variable organizational support factor has a significant effect on the performance of Grand Dian Hotel employees. The variable management support factor has a significant effect on the performance of Grand Dian Hotel employees. Variables of individual competence factors, organizational support factors, management support factors simultaneously together on the performance of Grand Dian Hotel employees.